Effect of Cl doping on the electrochemical performance of Sr2Fe1.5Mo0.5O6−δ cathode material for solid oxide fuel cells. Issue 14 (1st October 2020) - Zhang, Yanli; Zhu, Zongchao; Gu, Yiheng; Chen, Han; Zheng, Yifeng; Ge, Lin
Abstract: In this paper, a novel Cl − anion doping strategy is proposed to modify the electrochemical performance of Sr2 Fe1.5 Mo0.5 O6− δ (SFM) cathode for solid oxide fuel cells. A series of Cl-doped Sr2 Fe1.5 Mo0.5 O6− x − δ Cl x (SFMCl x, x  = 0, 0.1, 0.2, 0.3, 0.4) materials is synthesized by the citric acid–glycine combustion method, and the effect of Cl doping on the crystal structure and electrochemical performance is systemically investigated. The doping of Cl into the SFM leads to the lattice expansion, and the electrochemical performance of Cl-doped SFMCl x cathodes is effectively improved as a result of the enhanced mobility of lattice oxygen introduced by Cl doping. The optimal composition with x  = 0.2 (sample Sr2 Fe1.5 Mo0.5 O5.8− δ Cl0.2, noted as SFMCl0.2) exhibits a minimum polarization resistance Rp value of 1.987  Ω cm 2  at 600 °C, reduced by 38.04% compared with the SFM cathode. These results suggest that Cl doping is an effective strategy to improve the electrochemical properties of cathode for solid oxide fuel cells.